The Impact of National and School Contextual Factors on the Academic Performance of Immigrant Students - Finch, Holmes; Hernández Finch, Maria E.; Avery, Brooke (Frontiers in Education, 2021)
The issue of immigration has become central to the politics of nations across the world, impacting many aspects of life over the last decade. Researches investigating educational achievement through a cross-national lens have found that immigrant children tend to exhibit lower academic achievement than their native born peers, and that these differences are exacerbated by both family level variables (e.g., socioeconomic status) as well as the school climate. The goal of the current study was to build on earlier work in this area by investigating the nature and degree to which national attitudes towards immigration have changed over time, and whether any such changes were associated with academic achievement for immigrant and native born students. In particular, the relationship between changing attitudes towards immigration and the achievement gap between native and immigrant students. Results of the study demonstrated that nations with more negative attitudes towards refugees in general, and those for which these attitudes became more negative over time had greater achievement gaps than did those nations with more positive attitudes. In addition, these change trajectories moderated relationships between teacher attitudes towards multiculturalism and academic achievement.